The Euro and its Impact on ASEAN Economies - Chaiwoot Chaipan (Universität Hohenheim, Institut für Agrarpolitik und Landwirtschaftliche Marktlehre, 2000)
The launching of the EURO not only affects the members of EURO-Land, but it also affects the potential new member countries such as Central and Eastern European countries as well as some countries in Europe, Africa and French territories such as Monaco, San Marino, Vatican, Andorra, Mayotte, Saint Pierre, Miquelon, New Caledonia, and countries in West and Central Africa?s single-currency zone. These countries will adopt the EURO without belonging to the Union. And if Sweden, Denmark, Greece and Britain join the single currency, then their overseas territories would automatically adopt the EURO too. The EURO also influences third countries such as the United States, Japan and developing Asian countries. This paper looks at the conditions that will create EURO?s dominance in the ASEAN economies, and to what extent they will be threatened, or enhanced.
urn:nbn:de:bsz:100-opus-742
Keywords: 630; European Union; Economic and Monetary Union; Euro (Currency); Association of South-East Asian Nations; Euro; Eurozone; Internationales Währungssystem; Internationale Wirtschaftsbeziehungen; ASEAN-Staaten; EU-Staaten